Generic redescription, seven new species and a key to the Taphura Stål, 1862 (Hemiptera: Cicadidae: Cicadetttinae: Taphurini) - Sanborn, Allen F. (Zootaxa, 2017)
The Neotropical cicada genus Taphura Stål, 1862 is redescribed. Taphura attiguclava n. sp., Taphura cernuunca n. sp., Taphura crispula n. sp., Taphura demissa n. sp., Taphura dolabella n. sp., Taphura lanceola n. sp., and Taphura maccagnani n. sp. are described and illustrated. A summary of the 17 current species of Taphura along with the synonymic history and distribution of each species is provided. The first records of T. boulardi Sanborn, 2011 for Surinam, T. hastifera (Walker, 1858) for Bolivia and Ecuador, T. misella (Stål, 1854) for Bolivia and French Guiana, T. nitida (Degeer, 1773) for French Guiana, and T. sauliensis Boulard, 1971 for Ecuador and Trinidad & Tobago are provided. Finally, a key to the known species is provided.